Regulations in Mixed Marriage: A Comparative Review Between the Marriage Legal System In Indonesia and the Marriage Legal System in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2024)
According to Law Number 1 of 1974, a marriage is considered valid as long as it is carried out in accordance with religion or belief. Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family based on God Almighty. Mixed marriage is a marriage between two people who are subject to different laws due to differences in citizenship. This study uses a normative legal research approach that utilizes primary and secondary legal materials in its analysis so that the legal data used is secondary data or data that is not obtained directly such as law books, academic journals, and official documents. This study aims to analyze mixed marriages between Indonesian citizens and foreign citizens according to Law Number 1 of 1974 concerning Marriage and the marriage laws in force in Nigeria.